Clinico-Physiological and Haemodynamic Alterations Following Propofol Induction and Premedication with Butorphanol, Dexmedetomidine or Acepromazine in Dogs - Dewangan, Rukmani; Pal, Sumeet; Sharda, Raju; Tiwari, S. K.; Chaurasia, Durga; Khutey, B.B.; Ratre, H.K. (International Journal of Bio-resource and Stress Management, 2024)
The present study was conducted during February-October 2021 at Department of Veterinary Surgery and Radiology, College of Veterinary Science & A.H. Anjora, Durg (C.G.), India to evaluate the alternations on clinico-physiological and haemodynamic parameters following propofol induction in dogs premedicated with butorphanol or dexmedetomidine or acepromazine. Eighteen adult dogs of either sex were randomly divided into three groups (BP, DP and AP) with six animals in each. Ten minutes prior to the anaesthetic administration, all the dogs were administered glycopyrrolate @ 0.02 mg kg-1 I/M. The animals of group BP, DP and AP were premedicated intramuscularly with butorphanol @ 0.3 mg kg-1 b.wt., dexmedetomidine @ 10 µg kg-1 b.wt. and acepromazine @ 0.4 mg kg-1 b.wt. respectively. General anaesthesia was induced with propofol @ 7 mg kg-1 b.wt. intravenously. Clinical parameters were recorded following induction with propofol. Physiological and haemodynamic parameters were recorded before (0), 5 min. after sedation, induction and at 10, 20, 40, 60 and 120 min. post propofol anaesthesia. The onset of sedation and anaesthesia was quicker in group DP followed by AP and BP. Duration of anaesthesia and complete recovery were significantly (p<0.05) longer in group DP as compared to group BP and AP. The physiological and haemodynamic parameters showed transient changes which were compensated and remained within normal range during the study period without producing any deleterious effect. Thus, propofol can be safely used as induction agent in dogs premedicated with either dexmedetomidine or butorphanol or acepromazine and does not produce any adverse effect on cardiopulmonary system. However, dexmedetomidine-propofol combination provided longer duration of anaesthesia in dogs as compared to other groups.